TNNT2 Missplicing in Skeletal Muscle as a Cardiac Biomarker in Myotonic Dystrophy Type 1 but Not in Myotonic Dystrophy Type 2 - Bosè, Francesca; Renna, Laura Valentina; Fossati, Barbara; Arpa, Giovanni; Labate, Valentina; Milani, Valentina; Botta, Annalisa; Micaglio, Emanuele; Meola, Giovanni; Cardani, Rosanna (Frontiers in Neurology, 2019)
Cardiac involvement is one of the most important manifestations of the multisystemic phenotype of patients affected by myotonic dystrophy (DM) and represents the second cause of premature death. Molecular mechanisms responsible for DM cardiac defects are still unclear, however, missplicing of the cardiac isoform of troponin T (TNNT2) and of the cardiac sodium channel (SCN5A) genes might contribute to the reduced myocardial function and conduction abnormalities seen in DM patients. Since in DM skeletal muscle TNNT2 gene shows the same aberrant splicing pattern observed in cardiac muscle, the principal aim of this work was to verify if the TNNT2 aberrant fetal isoform expression could be secondary to myopathic changes or could reflect the DM cardiac phenotype. Analysis of alternative splicing of TNNT2 and of several genes involved in DM pathology has been performed on muscle biopsies from patients affected by DM type 1 (DM1) or type 2 (DM2) with or without cardiac involvement. Our analysis shows that missplicing of muscle specific genes is higher in DM1 and DM2 than in regenerating control muscles indicating that these missplicing could be effectively important in DM skeletal muscle pathology. When considering TNNT2 gene, missplicing appear to be more evident in DM1 than in DM2 muscles since in DM2 the TNNT2 fetal isoform appears to be less expressed than the adult isoform. This evidence does not seem to be related to less severe muscle histopathological alterations that appear to be similar in DM1 and DM2 muscles. These results seem indicate that the more severe TNNT2 missplicing observed in DM1 could not be related only to myopathic changes but could reflect the more severe general phenotype compared to DM2, including cardiac problems that appear to be more severe and frequent in DM1 than in DM2 patients. Moreover, TNNT2 missplicing significantly correlates with the QRS cardiac parameter in DM1 but not in DM2 patients indicating that this splicing event have good potential to function as biomarker of DM1 severity and it should be considered in pharmacological clinical trial to monitor the possible effects of different therapeutic approaches on skeletal muscle tissues.